2009
DOI: 10.3109/03639040903025848
|View full text |Cite
|
Sign up to set email alerts
|

Formulation and evaluation of natural gum-based sustained release matrix tablets of flurbiprofen using response surface methodology

Abstract: The formulated matrix tablets followed zero-order kinetics with negligible drug release in 0.1 N HCl at pH 1.2, which was the objective of this study to produce a formulation avoiding the gastric effects of flurbiprofen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(17 citation statements)
references
References 15 publications
1
15
0
Order By: Relevance
“…stretching, respectively. These FTIR studies are found to be in line with previous studies, suggesting that there was drug stability during the direct compression technique (Shah et al, 2009). …”
Section: Fourier Transform Infrared Spectroscopysupporting
confidence: 91%
See 2 more Smart Citations
“…stretching, respectively. These FTIR studies are found to be in line with previous studies, suggesting that there was drug stability during the direct compression technique (Shah et al, 2009). …”
Section: Fourier Transform Infrared Spectroscopysupporting
confidence: 91%
“…A CCD with α = 1.414 was employed as per the standard protocol (Shah et al, 2009;Singh et al, 2005c). The amounts of CP (X 1 ) and SCMC (X 2 ) were selected as the factors, which were studied at five levels each.…”
Section: Experimental Designmentioning
confidence: 99%
See 1 more Smart Citation
“…Such a behavior of dosage form effectively minimizes side effects and subsequently improves tolerability and adherence. Many researchers have sought to formulate matrices for zero-order release pattern, but few have been successful (25,40).…”
Section: Discussionmentioning
confidence: 99%
“…It reduces the number of experimental runs necessary to establish a mathematical trend in the experimental design allowing for the determination of the optimum level. Reducing the number of experiments by optimizing a formulation during development of a drug delivery device may also lead to significant reductions in production costs (20).…”
Section: Figurementioning
confidence: 99%